2003
DOI: 10.1074/jbc.m212819200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel and Specific Inhibitor for the Pro-apoptotic Protease Omi/HtrA2

Abstract: Omi/HtrA2 is a mammalian serine protease with high homology to bacterial HtrA chaperones. Omi/HtrA2 is localized in mitochondria and is released to the cytoplasm in response to apoptotic stimuli. Omi/HtrA2 induces cell death in a caspase-dependent manner by interacting with the inhibitor of apoptosis protein as well as in a caspase-independent manner that relies on its protease activity. We describe the identification and characterization of a novel compound as a specific inhibitor of the proteolytic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 21 publications
7
108
1
Order By: Relevance
“…Bacterially made HisOmi 134 -458 is an active serine protease and has been described previously (13). ucf-101 Inhibitor Prevents HAX-1 Degradation-We investigated whether the Omi protease is specifically responsible for the degradation of HAX-1 observed in HK-2 cells during apoptosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterially made HisOmi 134 -458 is an active serine protease and has been described previously (13). ucf-101 Inhibitor Prevents HAX-1 Degradation-We investigated whether the Omi protease is specifically responsible for the degradation of HAX-1 observed in HK-2 cells during apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…ucf-101 is a specific inhibitor of the proteolytic activity of Omi and has been described previously (13). When HK-2 cells were treated with cisplatin in the presence of ucf-101, the percentage of apoptotic cells decreased and the inhibitor significantly blocked HAX-1 degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten minutes before reperfusion, animals were randomized to receive vehicle (DMSO) or ucf-101 (1.5 mol/kg; estimated plasma concentrations, 20 mol/L) via intraperitoneal injection. Ucf-101 has been shown to inhibit 50 to 90 % of Omi/HtrA2 activity but has no effect on other proteases at these concentrations (Cilenti et al 2003).…”
Section: Experimental Protocolmentioning
confidence: 95%
“…These data indicate that under certain conditions Omi/HtrA2 may mediate cell death through its serine protease properties from within the mitochondria. Indeed, when we studied the subcellular localization of ucf-101 in neutrophils by utilizing the autofluorescent properties of this compound, 7 it was found that the ucf-101 red autofluorescence and the signal from the mitochondrial marker MitoTracker GreenFM colocalized (Figure 1e; a shift in fluorescence to yellow depicts colocalization). Colocalization was confirmed by semiquantitative analysis with the LSM510 Image software (Figure 1f), which showed the peaks of ucf-101 fluorescence (red) in close proximity with the peaks of MitoTracker fluorescence (green).…”
Section: Dear Editormentioning
confidence: 99%